Role of Secondary Prophylaxis with Valganciclovir in the Prevention of Recurrent Cytomegalovirus Disease in Solid Organ Transplant Recipients. (4th October 2017) - Gardiner, Bradley; Chow, Jennifer; Price, Lori Lyn; Nierenberg, Natalie; Kent, David; Snydman, David R
Abstract: Background: Reactivation of latent cytomegalovirus (CMV) infection is a major cause of morbidity and mortality in solid organ transplant recipients (SOTR). Ganciclovir and valganciclovir are highly effective antiviral drugs whose role in the treatment of CMV disease and primary prophylaxis is well established. The efficacy of secondary prophylaxis (SP) following the successful completion of CMV treatment is, however, not clear. The objectives of this study were to examine the effect of secondary prophylaxis with valganciclovir on the likelihood of relapse in SOTR who had completed treatment for an episode of CMV disease. Methods: We performed a single-center retrospective cohort study of SOTR from 1995–2015 and used propensity score based inverse probability of treatment weighting methodology to control for confounding by indication. A weighted Cox proportional hazards model was created to determine the effect of SP on time to relapse within 1 year of treatment completion. Results: A total of 52 heart, 34 liver, 79 kidney and 5 liver–kidney transplant recipients who were treated for an episode of CMV disease were included. One hundred and twenty (70.6%) received SP for a median duration of 61 days, with a range of 5–365 days. Thirty-nine patients (23%) relapsed. SP was protective against relapse from 0 to 6 weeks following treatment completion (hazard ratio, HR 0.19, 95% CI 0.05–0.69) but after 6 weeks risk of relapse did not significantly differ between the two groups (HR 1.18, 95% CI 0.46–2.99). Conclusion: Our findings demonstrate that patients who received SP with valganciclovir were significantly less likely to experience early relapse following treatment for CMV infection, but this benefit was not sustained long-term. This suggests that while SP is able to delay relapse, it has limited clinical utility in the overall prevention of recurrent CMV disease. Disclosures: D. R. Snydman, Merck: Scientific Advisor, Consulting fee; Shire: Scientific Advisor, Consulting fee